2009
DOI: 10.1002/eji.200939922
|View full text |Cite
|
Sign up to set email alerts
|

CCR6 and NK1.1 distinguish between IL‐17A and IFN‐γ‐producing γδ effector T cells

Abstract: cd T cells are a potent source of innate IL-17A and IFN-c, and they acquire the capacity to produce these cytokines within the thymus. However, the precise stages and required signals that guide this differentiation are unclear. Here we show that the CD24 low CD44 high effector cd T cells of the adult thymus are segregated into two lineages by the mutually exclusive expression of CCR6 and NK1.1. Only CCR6 1 cd T cells produced IL-17A, while NK1.1 1 cd T cells were efficient producers of IFN-c but not of IL-17A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
285
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(309 citation statements)
references
References 53 publications
24
285
0
Order By: Relevance
“…S6C). Furthermore, in agreement with published reports 45, 46 , we found that control IL-17 producing cells had a significantly higher CD44 MFI than IFNγ producing cells (Fig. S6D).…”
Section: Resultssupporting
confidence: 93%
“…S6C). Furthermore, in agreement with published reports 45, 46 , we found that control IL-17 producing cells had a significantly higher CD44 MFI than IFNγ producing cells (Fig. S6D).…”
Section: Resultssupporting
confidence: 93%
“…42: 1250Immunol. -1260 previously demonstrated [6,34] and characterized as a phenotype of IL-17 producers in the intestine [35]. However, whether the impairment of CCR6 + γδ T-lymphocyte accumulation by anti-CCL25 mAb during allergic pleurisy occurred via a direct mechanism (due to the coexpression with CCR9) or via an indirect mechanism is yet to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…This unique subset of lymphocytes can provide rapid tissue-specific immune responses, without the requirement of antiCorrespondence: Dr. Carmen Penido e-mail: cpenido@far.fiocruz.br gen presentation or clonal expansion, and is able to produce a large repertory of Th1-, Th2-, and Th17-associated cytokines [2][3][4][5][6]. These characteristics make γδ T cells a crucial first line of defense during infection, tissue damage, or stress.…”
Section: Introductionmentioning
confidence: 99%
“…Although IL‐23R is constitutively expressed on γδ 17 cells, the expression of IL‐1R in peripheral γδ 17 cells is tissue‐dependent 48. In addition to IL‐1R and IL‐23R, the expression of scavenger receptor 2 (Scart 2)49 and CCR6,27 and the lack of CD12225 and CD27 expression26 are often used as markers for γδ 17 cells, with the exception for IL‐17‐producing V γ 1 + γδ T cells 33. These phenotypes, established during thymic development, distinguish γδ 17 cells from IFN‐γ‐producing γδ T ( γδ IFN‐ γ ) cells (Fig.…”
Section: γδ T‐cell Subsets and Their Developmentmentioning
confidence: 99%